2023
DOI: 10.12973/eu-jer.12.2.1097
|View full text |Cite
|
Sign up to set email alerts
|

Study Item Parameters of Classical and Modern Theory of Differential Aptitude Test: Is it Comparable?

Abstract: <p style="text-align: justify;">This study aimed to find the Classical Test Theory (CTT) and Modern Test Theory (MTT) item parameters of the Differential Aptitude Test (DAT) and examined their comparability of them. The item parameters being studied are difficulty level and discrimination index. 5.024 data of the result sub-test DAT were documented by the Department of Psychology and Guidance and Counselling bureau. The parameter of classical and modern test items was estimated and correlated by examinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…CTT is considered widely used because it does not require a large number of respondents (more than 100) and is easy to understand and apply (Argianti & Retnawati, 2020). Setiawati et al (2023) revealed that for more than 20 years, CTT has been the mainstay standard in the development of psychological tests. Even though there are several advantages to CTT, there are things that make it have limitations.…”
Section: Introductionmentioning
confidence: 99%
“…CTT is considered widely used because it does not require a large number of respondents (more than 100) and is easy to understand and apply (Argianti & Retnawati, 2020). Setiawati et al (2023) revealed that for more than 20 years, CTT has been the mainstay standard in the development of psychological tests. Even though there are several advantages to CTT, there are things that make it have limitations.…”
Section: Introductionmentioning
confidence: 99%